ARTIKEL ILMIAH PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. RIAU MEDIA TELEVISI - Surbakti, Mawardi (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
ABSTRACT Â The purpose of this study was to determine the effect of leadership style to the work motivation in PT. Riau Media Television. This study uses a style of leadership and motivation as independent variables as the dependent variable. Indicators of leadership style in this study is authoritarian, participatory, and discretionary. Indicators used in the work motivation, boss, co-workers, facilities, policies and regulations, and in exchange for money and nonuang. This research was conducted at PT. Riau Media Television, the sample used is an employee of PT. Riau Media Television with a population of 97 where the number of samples is set as 97 respondents using saturated sample. Data were distributed to 97 employees of PT. Riau Media Television became the primary data source. The analysis includes the validity, reliability, and simple linear regression analysis. Data that has been using SPSS produce regression equation Y = 5219 + 0.243e. Thitung t test results obtained for 3295> Ttabel amounted to 1,638. Test the validity of the data declared all valid variables, and of the reliability test data for all variables expressed reliable. Based on the results of the t test performed and the results of simple linear regression analysis known that the style of leadership has positive influence on work motivation. Suggestions for PT. Riau Media Television is more concerned with its employees by giving rewards to employees performing so will increase the motivation of employees to contribute more to the company.